An analysis of Politeness Strategies in Indonesian English Textbooks - Ayu Meiratnasari; Agus Wijayanto; Suparno Suparno (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The research aimed explores politeness approaches in EFL textbooks, especially Indonesian English textbooks. There were two textbooks which analysed as the sample for this study. The textbooks entitled “Talk Active 1” and “Talk Active 2: Language and Culture Programme”. The researcher limited the analysis on the dialogs which provided as materials in the textbooks. Brown & Levinson's (1987) politeness strategies were applied to categorize the data. The researcher applied content analysis method proposed by Denscombe, (2010) as the research method. The results of the study revealed bald on-record, positive politeness, negative politeness, and off-record were reflected in the Indonesian English textbooks. Both types of bald on-record strategies were found in the Indonesian English textbooks. However, there were only three types of off-records strategies were reflected in the textbooks. The finding revealed 11 types of positive politeness as strategy follows: S1: Notice, attend to hearer; S2: Exaggerate, S3: Intensify interest to hearer; S4: Use in-group identity markers; S6: Avoid disagreement; S7: Presuppose/assert/raise common ground; S8: Joke; S10: Offer, promise; S12: Include both speaker and hearer in the activity; S13: Give (or ask for) reasons; S14: assume or assert reciprocity. The result also presented 8 types of negative politeness as follows: S1: Be conventionally indirect; S2: Question, hedge; S3: Be pessimistic; S4: Minimize the imposition; S5: Give deference; S6: Apologize; S7: Impersonalize speaker and hearer and S10: Go on record as incurring a debt, or as not indebting hearer. The analysis showed positive and negative politeness strategies were central strategies that reflected in the textbooks. It proved that Indonesian English textbooks have pragmatics input for the students.